A Scoping Review on Factors Affecting Cadaveric Decomposition Rates - Lai Poh Soon; Khoo Lay See; Nazni Wasi Ahmad; Kharmila Abdullah; Ahmad Hafizam Hasmi (Juniper Publishing Group, 2024)
Non-Indexed Publication